Forgetting Orpheus: Toward a Politics of Awakening - Carrieri, Alessandro (Aisthesis, 2025)
This brief essay, based on a Kracauerian consideration of the surface level as the result of both a specific dominant economic and political rationality and the struggle between conflicting social instincts and drives, aims to highlight how this surface has never stopped to affect and shape, in turn, specific individual and social behaviours. The convergence between the offer of innumerable forms of unreality adorned with illusory promises of salvation and the inexhaustible demand resulting from the absence of reality itself, which present society compensates for with surrogate and consolatory expedients, produces a rarefied and narcotizing atmosphere, what Günther Anders called an eschatological calm. If it ensnares all criticism and every action, even and especially in the face of catastrophic events threatening the very survival of humanity, the decoding of its dreamlike images can still unveil its phantasmagorical essence and open our eyes to the world in which we really live.